2013
DOI: 10.1016/j.ydbio.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin and integrin alpha 5 play requisite roles in cardiac morphogenesis

Abstract: Summary Fibronectin and its major receptor, integrin α5β1 are required for embryogenesis. These mutants have similar phenotypes, although, defects in integrin α5-deficient mice are milder. In this paper, we examined heart development in those mutants, in which the heart is formed, and discovered that both fibronectin and integrin α5 were required for cardiac morphogenesis, and in particular, for the formation of the cardiac outflow tract. We found that Isl1+ precursors are specified and migrate into the heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 41 publications
3
60
2
Order By: Relevance
“…Previous studies demonstrated that integrin α5β1 is a major Fn1 receptor in early and mid-gestation mouse embryos (Chen et al, 2015;George et al, 1997George et al, , 1993Mittal et al, 2013Mittal et al, , 2010Pulina et al, 2014Pulina et al, , 2011Takahashi et al, 2007;Yang et al, 1999Yang et al, , 1993. Therefore, we used conditional mutagenesis to ablate integrin α5 in the NC.…”
Section: Role Of Fn1 and Integrin α5 In Nc Development And Cardiovascmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that integrin α5β1 is a major Fn1 receptor in early and mid-gestation mouse embryos (Chen et al, 2015;George et al, 1997George et al, , 1993Mittal et al, 2013Mittal et al, , 2010Pulina et al, 2014Pulina et al, , 2011Takahashi et al, 2007;Yang et al, 1999Yang et al, , 1993. Therefore, we used conditional mutagenesis to ablate integrin α5 in the NC.…”
Section: Role Of Fn1 and Integrin α5 In Nc Development And Cardiovascmentioning
confidence: 99%
“…NC cells are known to express a number of Fn1 receptors, including αv-, α4-and α5-containing integrin heterodimers (Grazioli et al, 2006;Haack and Hynes, 2001;Testaz et al, 1999). Integrin α5β1 is thought to be a major Fn1 signal transducer during early to mid-gestation (George et al, 1997(George et al, , 1993Mittal et al, 2013Mittal et al, , 2010Pulina et al, 2014Pulina et al, , 2011Takahashi et al, 2007;Yang et al, 1999Yang et al, , 1993. Therefore, we asked whether integrin α5β1 was required for activation of Notch and differentiation of NC-derived cells into VSMCs.…”
Section: Fn1 Regulates Activation Of Notch and Nc Differentiation Intmentioning
confidence: 99%
“…In fact, ␣5␤1 FN interactions have been shown to be crucial for maintenance of mesodermal derivatives during postgastrulation stages and also for the survival of some NCCs (20). Integrin ␣5␤1 null embryos have cranial neural crest and endodermal cell death, which were shown to occur along their migration pathways (27). Although FN and FGF8 interaction has never been reported, binding of FN to its receptor ␣5␤1 has been shown to regulate FGF8 signaling in the pharyngeal arch region (27).…”
Section: Fibulin-1 Binds To Fgf8 and Their Effect On Embryo Developmentmentioning
confidence: 99%
“…Integrin ␣5␤1 null embryos have cranial neural crest and endodermal cell death, which were shown to occur along their migration pathways (27). Although FN and FGF8 interaction has never been reported, binding of FN to its receptor ␣5␤1 has been shown to regulate FGF8 signaling in the pharyngeal arch region (27). Because FBLN1 is a major binding partner of FN (28), it is possible that the FBLN1 effects on NCC migration might be regulated through partnership with FN along the migration paths from the hindbrain.…”
Section: Fibulin-1 Binds To Fgf8 and Their Effect On Embryo Developmentmentioning
confidence: 99%
“…Integrin-α5 KO mice die at E10.5 with severe vascular defects (Yang et al, 1993;Francis et al, 2002;Mittal et al, 2013), whereas genetic ablation of all five αv integrins leads to placental defects and haemorrhaging within the brain (Bader et al, 1998). Endothelium-specific deletion of both α5 and αv subunits, however, fails to replicate the angiogenic defects observed in global KO-mice, but instead leads to defects in the remodelling of the heart and great vessels (van der Flier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%